The Relationship between Professional Competencies, Job Satisfaction and Job Performance among University Counselors in China: A Conceptual Paper - Jie, Cao; Naha Abu Mansor, Nur; Widarman Yus Kelana, Beni (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this paper is to study the relationship between professional competencies, job satisfaction, and job performance among university counselors in China through literature review. Although research has been carried out on counselors' professional competencies and job performance, and their job satisfaction has also caused the attention of researchers, the study of the relationship among these three variables is still neglected, and these are all essential to university counselors. This research uses the previous literature as the main data. Moreover, it aims to summarize the existing literature containing issues of professional competencies, job satisfaction, and job performance among university counselors and tries to provide a conceptual framework for further research.